Relationship between the lability of sediment-bound Cd and its bioaccumulation in edible oyster. Issue 1 (15th November 2015) - Chakraborty, Parthasarathi; Ramteke, Darwin; Chakraborty, Sucharita; Chennuri, Kartheek; Bardhan, Pratirupa
Abstract: A linkage between Cd speciation in sediments and its bioaccumulation in edible oyster ( Crassostrea sp .) from a tropical estuarine system was established. Bioaccumulation of Cd in edible oyster increased with the increasing lability and dissociation rate constants of Cd-sediment complexes in the bottom sediments. Total Cd concentration in sediment was not a good indicator of Cd-bioavailability. Increasing trace metal competition in sediments increased lability and bioavailability of Cd in the tropical estuarine sediment. Low thermodynamic stability and high bioavailability of Cd in the estuarine sediment were responsible for high bioaccumulation of Cd in edible oysters (3.2–12.2 mg kg − 1 ) even though the total concentration of Cd in the bottom sediment was low (0.17–0.49 mg kg − 1 ). Graphical abstract: Highlights: A linkage between Cd speciation and bioavailability in sediments was established. Total Cd in sediment was not a good indicator of Cd-bioavailability. Bioaccumulation of Cd increased with increasing lability of Cd-complexes. Increasing trace metal competition in sediments increased bioavailability of Cd. Low Cd in sediment may increase Cd bioaccumulation in oyster.